PENERAPAN TEKNIK ROLE PLAY UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS 1 SMP NEGERI 9 BINTAN - Suyenny '; Hadriana '; Novitri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research is aimed to find out whether there is a significant effect of students’ speaking ability after using Role Play technique in teaching speaking at the first year students of SMP Negeri 9 Bintan. The research problem is: Can the application of role play technique improve the speaking ability of the first year students of SMP Negeri 9 Bintan?. The design of the research was one group pretest-posttest design and the research was conducted at SMP Negeri 9 Bintan. Cluster random sampling method was used to select one class of students to become the sample. As a result, 34 students of class VIIB at the first semester of academic year 2016/2017 were chosen as the samples. The steps applied in using role play technique are: (1) The teacher introduced the activity by explaining the material, making sure that all the students understand it (2) Teacher and students discussed about relevant vocabulary, sentences, or dialogues based on the material (3) Students were divided into groups (4) The teacher gave role card for each students to act out (5) The students familiarize themselves with their roles in a few minutes (6) Students constructed the dialogue based on their roles with their friends and practiced their own dialogue in a few minutes to familiarize them with the language (7) Teachers let the students act out the role play and exchanged their roles without interrupting or correcting (8) Teacher evaluated and checked students’ comprehension. The instrument used was a speaking test and the obtained data was analyzed by using SPSS version 21.0 for Windows. The results of data analysis are t-test (17.16) was higher than t-table (2.042). This indicates that there is a significant effect of students’ speaking ability after being taught using Role Play technique in teaching speaking.